AN ANALYSIS OF SPEECH ACT IN ADVERTISING OF CHILD MILK ON TELEVISION - Novianti, Fitri; Maliyani, Regina Ratna Dewi (PROJECT (Professional Journal of English Education), 2018)
Making the advertisement is like we do communication with the others. In speech act, there are words include the meaning to convey the message to the viewers. The aim of this research is to describe the type of act of illocutionary and to analyze the most dominant illocutionary function produced in the advertising. This research is a descriptive research. The subject of this research is child milk advertising on television namely Bebelac 3, Nutrilon Royal 3, and Pediasure. The object of this research is a form of act illocutionary functions contained in advertising speech. Data acquisition uses note technique. Based on the analysis, the researchers get conclusion that the types of act illocutionary found in child milk advertising on television are declarative, representative, expressive, and commisive. In a child milk advertising on television, illocutionary function shows dominance representative and commisive. In the representative, this indicates the presence of a statement and affirmation. Moreover, in the commisives, this indicates the speaker give the promise to the viewers. Keywords:  Pragmatic, Speech act, Advertising